A comparative study of selected bankruptcy prediction models in insurance companies listed on the Tehran Stock Exchange - Atefeh Safajoo; Hoda Hemmati (New Applied Studies in Management, Economics & Accounting, 2019)
The purpose of this study is a comparative study of selected models for predicting bankruptcy of insurance companies. The statistical population includes all insurance companies listed on the Tehran Stock Exchange and OTC in the period 2012 to 2016. The sample population includes 16 insurance companies. In this study, the risk of bankruptcy is considered based on the financial wealth index calculated by the Central Insurance of Iran and based on the Altman, Falmer, Zimsky and Springgate models, which the bankruptcy of companies is predicted. Eview software was used to analyse the data. The results show that there is a positive and significant relationship between the probability of bankruptcy risk based on Altman, Falmer, Zimsky and Springgit models with the risk of bankruptcy of insurance companies, which shows these models can be applied to predict the bankruptcy of insurance companies. The results also show that there is no significant difference between the predictions of different models of bankruptcy risk prediction and the preference of models is indefinite.